Community participation and communication processes in the implementation of programs of resettlement of families within the context of urban development in the city of barranquilla (Colombia) (2016)
Planning processes of development and growth of the city of Barranquilla have required the relocation of the population living in areas of intervention actions. As part of the implementation of the New Management Plan Territorial (POT), the city plans to revitalize an area around the Magdalena River with a view to improving the quality of life of citizens and to increase competitiveness of the city. The revitalization project is known as project “La Loma “. Under the current Land Use Plan of Barranquilla (POT), the urban development project “La Loma” includes, among other activities, the transfer of a large number of people currently living in this area. For this reason, this article aims to review the current POT and documents from City Council and the Mayor’s office associated with the POT and “La Loma” project, in order to identify and analyze the component of community participation and communication related to the implementation of this project. The results of the documents revealed the presence of regulatory elements associated with community participation. The results also showed potentially useful spaces for the implementation of inclusive communication processes. Therefore, this article proposes a guide for the formulation of a strategic communication plan with a focus on participatory communication and dialogue facilitator to be used during the execution of urban projects that include the relocation of families. © 2016, Universidad del Norte. All rights reserved.